Reflection on Teachers’ Personal and Professional Growth Through a Materials Development Seminar - Astrid Núñez Pardo; María Fernanda Téllez Téllez (HOW, 2015)
This qualitative action research study explores the role of reflection on teachers’ personal and professional growth through the methodology used in the Materials Development Seminar in the Master’s Programme in Education with Emphasis on English Didactics at a private university in Colombia. The project was carried out with 31 English as a Foreign Language Teachers. The instruments for data gathering were a survey and a written reflection. The findings suggest that reflection is critical in raising teachers’ awareness of personal and professional growth, creating a reflective learning environment and a positive affective state. Additionally, a number of English as a foreign language teachers became text developers with a recognised Colombian publishing house.